Odpowiedzi

2009-12-11T15:12:37+01:00
Układ równań

5x+3y=0
-x -2y=7 / * 5

5x+3y=0
-5x -10y=35

-7y = 35 / : (-7)
y = - 5

5x+3y=0

5x + 3 * (-5) = 0

5x = 15 / : 5
x = 3


x= 3
y= -5




2009-12-11T15:13:23+01:00
5x+3y=0
{
-x-2y=7

5x+3y=0
{
-x=7+2y /÷(-1)

5x+3y=0
{
x=-7-2y

5(-7-2y)+3y=0
{
x=-7-2y

-35-10y+3y=0
{
x=-7-2y

-7y=35 /÷(-7)
{
x=-7-2y

y=-5
{
x=-7-2×(-5)

y=-5
{
x=3
2009-12-11T15:19:18+01:00
{5x+3y=0
{-x-2y=7 / ×5

{5x+3y=0
{-5x-10y=35

5x z -5x się redukuje

-7y=35 /÷ (-7)
y=-5

aby wyliczyć x podstawiamy do pierwszego

5x+3×(-5)=0
5x-15=0
5x=15 /÷5
x=3